A review of multiple input DC-DC converter topologies linked with hybrid electric vehicles and renewable energy systems - Azuka, Affam; Yonis M Yonis, Buswig; Al-Khalid, Hj Othman; Norhuzaimin, Julai; Ohirul, Qays (sciencedirect, 2021)
In this paper, the contemporary development in multiple input dc-dc converters are identified and examined. The quest to mitigate the difficulties associated with employing renewables in distribution systems and electric vehicles (EVs) has yielded many new converter topologies. These new topologies have easier control, lower parts count, are cheaper and are worthy alternatives to the typical series or parallel connection of converters. The converters are identified by three divisions that bother on the isolation between the respective ports. The electrically connected converters do not have isolation between the ports, and thus, a dc link connects the ports. Electromagnetically connected converters use a dc-link to connect input ports, but the input ports and output port are isolated. In magnetically connected converters, input ports are separated by multiple winding transformer, just as the output port is isolated from the input ports by the winding. The formation, structure, characteristics, operation, merits and demerits of the converters will be presented. Thereafter, comparisons will be done based on the distinct features of the converters. This review identifies that converter properties depend on the specific application requirement and thus, no converter fulfills all demands in the industry. Prospective future research trends are suggested. This work aims to update on research done during the time gap since the last comprehensive reviews.